Process of Conversion in Kurdish and Persian Languages from the Perspective of Morpheme-based Morphology - Darya Sabir Hamad; Sherwan Husen Hamad; Yadgar Karimi (QALAAI ZANIST JOURNAL, 2024)
This The title of the study is (Process of Conversion in Kurdish and Persian Languages from the Perspective of Morpheme-based Morphology). The main purpose of this study is to present the process of conversion in the interpretation of Kurdish and Persian words from the perspective of morpheme-based morphology, and how morphemes are arranged together to form words. Then it presented these similarities and differences between the two languages within the framework of the process of conversion. In this theory, the main unit of morphological analysis is the morpheme, which is a smaller unit than the word. The theory of morpheme-based morphology is also related to the method of combining morphemes in the sense that simple words are seen as a series of morphemes combined together, so in this theory, morphology can be introduced as the syntax of morphemes. In addition, within the framework of Kurdish and Persian languages, we have taken some words that are interpreted and analyzed by this theory, and we have also presented the types of conversion processes in Persian and Kurdish languages. Undoubtedly, some of the conversion processes are effective and productive, while others are ineffective and unproductive.